PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP SEMANGAT KERJA KARYAWAN PT. RIAU MUDA JASA SARANA PEKANBARU - Andy Riawan; Susi Hendriani; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted at PT. Riau Muda Jasasarana Pekanbaru with the aim of analyzing the influence of leadership and compensation on employee morale. The study population was all employees of the company, amounting to 71 people. Determination of the census sample. Data analysis methods used are descriptive and multiple regression analysis using SPSS 17 for windows. The results showed that leadership and compensation have a significant effect simultaneously and partially on morale. Compensation is a dominant factor affecting employee morale. Morale of 98.5% can be explained by the variation that occurs in leadership and variable compensation. Recommendations can be given is that the management of the company to implement new aspects of leadership, especially leadership ability in forming cooperation, provide guidance and motivation to subordinates. In terms of compensation, most aspects need to be improved is the distribution of proportional bonus, fair and consistent.Keywords: Morale, Leadership and Compensation